Commonly Transmitted HIV-1 Drug Resistance Mutations in Reverse-Transcriptase and Protease in Antiretroviral Treatment–Naive Patients and Response to Regimens Containing Tenofovir Disoproxil Fumarate or Tenofovir Alafenamide. (30th January 2017) - Margot, Nicolas A.; Wong, Pamela; Kulkarni, Rima; White, Kirsten; Porter, Danielle; Abram, Michael E.; Callebaut, Christian; Miller, Michael D.
Abstract: Background: The presence of transmitted drug resistance mutations (TDRMs) in antiretroviral treatment (ART)–naive patients can adversely affect the outcome of ART. Methods: Resistance testing was conducted in 6704 ART-naive subjects predominantly from the United States and Europe in 9 clinical studies conducted by Gilead Sciences from 2000 to 2013. Results: The presence of TDRMs increased during this period (from 5.2% to 11.4%), primarily driven by an increase in nonnucleoside reverse-transcriptase (RT) inhibitor (NNRTI) resistance mutations (from 0.3% to 7.1%), particularly K103N/S (increase from 0.3% to 5.3%). Nucleoside/nucleotide RT inhibitor mutations were found in 3.1% of patients. Only 1 patient had K65R (0.01%) and 7 had M184V/I (0.1%), despite high use of tenofovir disoproxil fumarate (TDF), emtricitabine, and lamivudine and potential transmission of resistance to these drugs. At least 1 thymidine-analogue mutations was present in 2.7% of patients with 0.07% harboring T215Y/F and 2.7% harboring T215 revertant mutations (T215rev). Patients with the combination of M41L + L210W + T215rev showed full human immunodeficiency virus RNA suppression while receiving a TDF- or tenofovir alafenamide–containing regimen. Conclusions: There was an overall increase of TDRMs among patients enrolling in clinical trials from 2000 through 2013, driven primarily by an increase in NNRTI resistance. However, the presence of common TDRMs, including thymidine-analogue mutations/T215rev, showed no impact on response to TDF- or tenofovir alafenamide–containing regimens.